Close social relationships and happiness in the United States: the moderating role of love by God - Moller, Stephanie (Frontiers in Public Health, 2025)
In the contemporary United States, many individuals suffer from a lack of close relationships, negatively affecting their happiness. At the same time, many individuals do not feel a loving relationship with God/Spirit (i.e., religious love). In the 1950s, theorist Pitirim Sorokin posited that love, particularly religious love, acts as a transformative energy capable of fostering resilience in the modern rational world, and scholars hypothesized a link between religious love and happiness. However, the topic remains understudied. This study analyzes United States data from the Global Flourishing Study and presents results from linear regression with robust standard errors. The findings indicate that a central component of religious love, love by God, mitigates the adverse effects of lacking close relationships. This study calls on researchers to further investigate the significant yet understudied role of religious love in individuals’ lives.